Aspects of Onomastics in Ngwa Igbo: Preliminary Notes - Obinna, Patrick, Kenneth; Stephenie, Osondu, Amarachi; Ugonna N., Ofoha, (Journal of Language Development and Linguistics, 2024)
It is in this light that the researcher provides preliminary explanations on the sound, formation and meaning of Ngwa toponyms (place names) and Ngwa anthroponyms (personal names), as they occur in the Ngwa dialect of the Igbo Language. The primary means of data collection adopted in this study is the oral interviews of Key Informants (indigenous Ngwa people). Secondarily, data were collected from already existing literature on the subject matter. Data gotten are analyzed linguistically, using the basic provisions of phonology, morphology, syntax and semantics. Phonologically, the study establishes that the phonological nuances of aspiration, which is a characteristic feature of the Ngwa Igbo is also actively represented in their toponyms and anthroponyms. Other generative phonological processes such as assimilation, deletion and elision were shown to exist in the Ngwa names. Morpho-syntactically, the study shows that Ngwa toponyms and anthroponyms are associative constructions of two or more nominals which bear the semantics of the names. The study concludes that Ngwa anthroponyms and toponyms, properly analysed, bear in them the history, features and culture of the Ngwa people, and is a snippet into the past life of the Ngwa people.